Das Hochgebirgsland von Semyen: Begleitworte zu einer topographischen Karte 1: 50 000 - Werdecker, Josef (ERDKUNDE, 1968)
The accompanying topographic map represents the central part of the Semyen Highlands (rising to 4550 metres) in northern Ethiopia. On several expeditions between 1954 and 1964 the area (930 sqkm. or 359 sqmiles) was surveyed and mapped, both by surface and photogrammetric techniques. The determination of altitude yielded a value for the highest mountain in Ethiopia some 70 metres lower than had until now been assumed. This corresponds weil with the new value calculated by the US Coast and Geodetic Survey. The cartographic presentation has becn carried out by LEONHARD BRANDSTÄTTER, using the system which he himself has developed. His basic assumptions and recommendations for a new form for large-scale maps are commented upon, using the map under review.